2019
DOI: 10.1101/685271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective base excision repair in the response to DNA damaging agents in triple negative breast cancer

Abstract: 21 22 23DNA repair defects have been increasingly focused on as therapeutic targets. In hormone 24 positive breast cancer, XRCC1-deficient tumors have been identified and proposed as 25 targets for combination therapies that damage DNA and inhibit DNA repair pathways. 26XRCC1 is a scaffold protein that functions in base excision repair (BER) by mediating 27 essential interactions between DNA glycosylases, AP endonuclease, poly(ADP-ribose) 28 polymerase 1, DNA polymerase β (POL β), and DNA ligases. Loss of X… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…MDA-468 showed high expression levels of BER factors, including APE1, FEN1, PARP1, POLβ, and XRCC1, consistent with the high BER capacity and resistance to alkylating DNA damage observed previously. 13 Low oxidative DNA damage repair capacity was reported previously for several TNBC cell lines, including the four cell lines in this study, consistent with the low expression of OGG1 and NEIL family proteins in these cell lines. 17 We next evaluated repair by the NER pathway.…”
Section: Characterization Of Dna Repair Defects In Tnbc Cell Linessupporting
confidence: 92%
See 3 more Smart Citations
“…MDA-468 showed high expression levels of BER factors, including APE1, FEN1, PARP1, POLβ, and XRCC1, consistent with the high BER capacity and resistance to alkylating DNA damage observed previously. 13 Low oxidative DNA damage repair capacity was reported previously for several TNBC cell lines, including the four cell lines in this study, consistent with the low expression of OGG1 and NEIL family proteins in these cell lines. 17 We next evaluated repair by the NER pathway.…”
Section: Characterization Of Dna Repair Defects In Tnbc Cell Linessupporting
confidence: 92%
“…We previously used the flow cytometric host cell reactivation assay (FM-HCR) to characterize the BER repair capacity of a panel of commonly used TNBC cell line models, MDA-157, MDA-231, HCC1806, and MDA-468. 13 From this analysis, we observed that MDA-468 cells were the most BER competent of the four cell lines. 13 The previous BER analysis primarily evaluated lesion recognition by DNA glycosylases.…”
Section: Characterization Of Dna Repair Defects In Tnbc Cell Linesmentioning
confidence: 86%
See 2 more Smart Citations
“…High expression of APE1 in tumors was associated with the resistance to platinum and radiotherapy 39,40 . XRCC1 downregulated in gastric cancer, lung cancer and cervical cancer was associated with tumor invasion and poor prognosis 41‐43 . Furthermore, polβ mutations were found to be associated with tumor susceptibility 44,45 …”
Section: Discussionmentioning
confidence: 99%